(untitled) (Research, Society and Development, 2024)
Objective: To analyze the epidemiological profile of burn-related deaths in the state of Piauí between the years 2016 and 2021. Methodology: Epidemiological study of retrospective descriptive analysis of burn-related deaths in the state of Piauí, collected from the Mortality Information System (SIM). Causes of burns were considered: thermal, electrical, and other causes (chemical, frostbite, radiation). The analyzed criteria were: year of the accident, cause, age, gender, and location of occurrence. Descriptive and bivariate statistical analysis was performed to verify the statistical association between variables. Results: In Piauí, there were 379 burn-related deaths, mainly due to electrical causes, followed by thermal burns and other causes. There was an increase in the mortality rate between 2019 and 2021. Electrical and thermal burns are more prevalent in the adult population. Among children, the main cases of thermal burns occurred mainly during pandemic periods. Burns from other causes are more related to exposure to ultraviolet light. Overall, males are more affected in all types of burns. Among locations, the main cases of burns occur at home, during work, or in a hospital setting, with electrical burns being the most common type. Conclusion: The results found in this study serve as an initial overview of the epidemiological profile of burn-related deaths in the state of Piauí, providing support for more in-depth analyses on the subject and for the development of prevention and damage control strategies to reduce the impact on society.